Screening of the hearing of newborns - Update - Schnell-Inderst, Petra (German Medical Science GMS Publishing House, 2006)
INTRODUCTION: Permanent congenital bilateral hearing loss (CHL) of moderate or greater degree (≥40 dB HL) is a rare disease, with a prevalence of about 1 to 3 per 1000 births. However, it is one of the most frequent congenital diseases. Reliance on physician observation and parental recognition has not been successful in the past in detecting significant hearing loss in the first year of life. With this strategy significant hearing losses have been detected in the second year of life. With two objective technologies based on physiologic response to sound, otoacoustic emissions (OAE) and auditory brainstem response (ABR) hearing screening in the first days of life is made possible. OBJECTIVES: The objective of this health technology assessment report is to update the evaluation on clinical effectiveness and cost-effectiveness of newborn hearing screening programs. Universal newborn hearing screening (UHNS) (i), selective screening of high risk newborns (ii), and the absence of a systematic screening program are compared for age at identification and age at hearing aid fitting of children with hearing loss. Secondly the potential benefits of early intervention are analysed. Costs and cost-effectiveness of newborn hearing screening programs are determined. This report is intended to make a contribution to the decision making whether and under which conditions a newborn hearing screening program should be reimbursed by the statutory sickness funds in Germany. METHODS: This health technology assessment report updates a former health technology assessment (Kunze et al. 2004 [1]). A systematic review of the literature was conducted, based on a documented search and selection of the literature using predefined inclusion and exclusion criteria and a documented extraction and appraisal of the included studies. To assess the cost-effectiveness of the different screening strategies in Germany the decision analytic Markov state model which had been developed in our former health technology assessment report was updated. RESULTS: Universal newborn hearing screening programs are able to substantially reduce the age at identification and the age at intervention of children with CHL to six months of age in the German health care setting. High coverage rates, low fail rates and - if tracking systems are implemented – high follow-up-rates to diagnostic evaluation for test positives were achieved. New publications on potential benefits of early intervention could not be retrieved. For a final assessment of cost-effectiveness of newborn hearing screening evidence based long-term data are lacking. Decision analytic models with lifelong time horizon assuming that early detection results in improved language abilities and lower educational costs and higher life time productivity showed a potential of UNHS for long term cost savings compared to selective screening and no screening. For the short-term cost-effectiveness with a time horizon up to diagnostic evaluation more evidence based data are available. The average costs per case diagnosed range from 16,000 EURO to 33,600 EURO in Germany and hence are comparable to the cost of other implemented newborn screening programs. Empirical data for cost of selective screening in the German health care setting are lacking. Our decision analytic model shows that selective screening is more cost-effective but detects only 50% of all cases of congenital hearing loss. DISCUSSION: There is good evidence that UNHS-Programs with appropriate quality management can reduce the age at start of intervention below six months. Up to now there is no indication of considerable negative consequences of screening for children with false positive test results and their parents. However, it is more difficult to prove the efficacy of early intervention to improve long-term outcomes. Randomized clinical trials of the efficacy of early intervention for children with CHL hearing losses are inappropriate because of ethical reasons. Prospective cohort studies with long-term outcomes of rare diseases are costly, take a long time and simultaneously substantial benefits of early intervention for language development seem likely. CONCLUSIONS: A UNHS-Program should be implemented in Germany and be reimbursed by the statutory sickness funds. To achieve high coverage and because of better conditions for obtaining low false positive rates UNHS should be performed in hospital after birth. For outpatient deliveries additionally screening measures in an outpatient setting must be provided.